San Gerónimo Zacualpa: Indians Village, Sugar Cane Mill and Pious Work (Chiapas, 1660-1725) - Barrera Aguilera, Óscar Javier (2022)
Here we present some specific aspects of the change in the use, possession and rent of the communal lands that once belonged to the Indians of the village of Zacualpa, throughout the 17th century. We start with some generalities regarding the legal and administrative universe that were shared by the kingdoms of the West Indies sheltered by the Spanish empire. Then, we immerse ourselves in the province of Los Llanos to show its geographical, political, economic and cultural peculiarities. The bulk of this work is the analysis of a dozen of archival files that account for the fluctuations in the possession and administration of the land located in Zacualpa: a disappeared village of the Central Depression of Chiapas. The connecting thread is the legal mechanisms that allowed these agrarian transactions. Our methodological bet is to illustrate the combination of different legal orders in the midst of changing social relationships.